Prostate volume index and prostatic chronic inflammation have an effect on tumor load at baseline random biopsies in patients with normal DRE and PSA values less than 10 ng/ml: results of 564 consecutive cases. (August 2019) - Porcaro, Antonio B.; Tafuri, Alessandro; Sebben, Marco; Shakir, Aliasger; Novella, Giovanni; Pirozzi, Marco; Processali, Tania; Rizzetto, Riccardo; Amigoni, Nelia; Tiso, Leone; Cerrato, Clara; Brunelli, Matteo; et al.
Background: To assess the association of prostate volume index (PVI), defined as the ratio of the central transition zone volume (CTZV) to the peripheral zone volume (PZV), and prostatic chronic inflammation (PCI) as predictors of prostate cancer (PCA) load in patients presenting with normal digital rectal exam (DRE) and prostate-specific antigen (PSA) ⩽ 10 ng/ml at baseline random biopsies. Methods: Parameters evaluated included age, PSA, total prostate volume (TPV), PSA density (PSAD), PVI and PCI. All patients underwent 14 core transperineal randomized biopsies. We considered small and high PCA load patients with no more than three (limited tumor load) and greater than three (extensive tumor load) positive biopsy cores, respectively. The association of factors with the risk of PCA was evaluated by logistic regression analysis, utilizing different multivariate models. Results: 564 Caucasian patients were included. PCA and PCI were detected in 242 (42.9%) and 129 (22.9%) cases, respectively. On multivariate analysis, PVI and PCI were independent predictors of the risk of detecting limited or extensive tumor load. The risk of detecting extensive tumor load at baseline biopsies was increased by PSAD above the median and third quartile as well as PVI ⩽ 1 [odds ratio (OR)=1.971] but decreased by PCI (OR=0.185; 95% CI: 0.088–0.388). Conclusions: Higher PVI and the presence of PCI predicted decreased PCA risk in patients presenting with normal DRE, and a PSA ⩽ 10 ng/ml at baseline random biopsy. In this subset of patients, a PVI ⩽ or >1 is able to differentiate patients with PCA or PCI.